The Characteristic of Pregnancy in Woman with Rheumatic Mitral Stenosis in Dr. Soetomo Hospital Surabaya from 2015 – 2017 - Relmasira, Joseph; Wicaksono, Budi (UNUSA Press, 2020)
Background: Cardiac disease is 1 of the major causes of maternal mortality. Mitral Stenosis (MS) is a particularly high-risk condition for a pregnant woman in emerging countries, the main cause of MS is a complication from rheumatic heart disease. Objective: To study the maternal and perinatal outcome of pregnancies complicated by mitral stenosis from rheumatic heart disease. Methods: We conduct a cross-sectional retrospective study using electronic medical data records in dr. Soetomo General Hospital over the period of 3 years from 2015 – 2017 involving 36 cases of pregnant women complicated by rheumatic mitral stenosis. The maternal and perinatal outcome was reviewed. Result: Most of the pregnant women with rheumatic mitral stenosis were at 29 - 34 weeks of gestational age. Majority of the patient (61,1 %) was in NYHA II classification for heart failure degree. The Degree of MS was moderate (75 %) and severe (25 %), with a maternal mortality rate was 4/36 patients (11,1 %), and all of the patients were with severe MS had class III/IV heart failure. The main reason for hospital admission was heart failure (50 %). 38 % of women with NYHA Class III/IV had severe MS. Most accompanying valve diseases occur at the patient with severe MS, with Tricuspid Regurgitation as the most accompanying valve disease (66,67 %) followed by Mitral Regurgitation (36,11 %) and Aortic Regurgitation (25 %). Percutaneous Transmitral Valve Commissurotomy (PTMC) was the chosen surgical intervention for valve correction. For a patient with Moderate MS, 6/8 (75 %) of the pregnancy terminated at ³ 34 weeks of gestational age, compared with 18/28 (64,28 %) patient with Severe MS the pregnancy terminated at < 34 weeks of gestational age. Cesarean section was the most chosen method of delivery for most of the cases. Fetal weight (4/7 cases) at delivery for Moderate MS was > 2500 g, compared with (7/18 cases) was < 2000 g for Severe MS. APGAR Score for Moderate MS cases was 8-10 for 5/7 cases, compared with Severe MS, 16/24 cases were < 8. Conclusions: Cardiac and obstetric complications from rheumatic mitral disease remain a major challenge in this disease. Early diagnosis and management with good adherent to pre-conceptional and prenatal care remain a key factor for preventing maternal and fetal morbidity and mortality.